Analisis Pajak Pertambahan Nilai (PPN) dan Pajak Penghasilan Pasal 22 Atas Barang Impor Terhadap Pajak Terutang : Studi Empirik Pada PT Saranaprima Nusantara Abadi - Dina Triani; Mari Sri Utami (Mulia Pratama, 2023)
PT Saranaprima Nusantara Abadi is a company engaged in the packaging industry made from flexible plastic or flexible packaging (flexible packaging). This study uses quantitative and descriptive methods to find out whether Value Added Tax and Article 22 Income Tax on Import against Taxes Payable are in accordance with laws and regulations, especially those governing the calculation, collection, and reporting of Value Added Tax and Article 22 Income Tax on Import conducted by PT Saranaprima Nusaantara Abadi in 2022. In this study, the author uses data in the form of tax invoices, notification letters (SPT) for the period of Value Added Tax, and Goods Import Notifications (PIB). Based on the results of the research, it was concluded that the calculation and reporting of Value Added Tax and Article 22 Import Income Tax carried out by PT Saranaprima Nusantara Abadi were not fully in accordance with the applicable laws and regulations. In Value Added Tax there are several calculation errors caused by defective and expired tax invoices and incorrect VAT rates. Whereas for Import Income Tax Article 22 there is ignorance in using the exchange rate in accordance with Customs calculations and ignorance of crediting Article 22 Income Tax as a reduction of Payable Tax. In connection with this problem, PT Saranaprima Nusantara Abadi should be able to calculate and report Value Added Tax and Article 22 Import Income Tax in accordance with the latest tax provisions, such as the Law on Harmonization of Tax Regulations and Minister of Finance Regulations. Keywords: Value Added Tax, Income Tax Article 22 on Import, Tax Payable